Procurement guidelines (Asian Developmennt Bank (ADB), 2006)
This publication serves to inform those carrying out a project that is financed in whole or in part by a loan from the Asian Development Bank (ADB), ADB-financed grant, or ADB-administered funds, of the policies that govern the procurement of goods, works, and services required for the project.